Machine Learning Prediksi Karakter Pengguna Hastag (#) Bahasa Generasi Milenial Di Sosial Media - Anita Sindar RM Sinaga (IJAI (Indonesian Journal of Applied Informatics), 2020)
Activity on the internet leaves a traceable digital trail. Users who are expressive of social media and have a habit of pouring everything on Instagram are more considerate of the cause and effect of status updates. The problem discussed in this study is to describe the character of the Instagram user account according to the hashtags (#) of the most widely used millennial language such as #awesome and so on. With machine learning, computers can work alone. This digital technology has long been applied to Google search, search engines and social media (Facebook, Twitter, Instagram). The benefits of machine learning are the ease of obtaining digital data from online users. The stages of the study consisted of the application of algorithms that produced predictions for classification using the K-Nearest Neighbors Algorithm. The formulation of the problem in this research is how to process data sourced from millennial language hashtags based on the most popular hashtags (#) on instagram using machine learning by identifying names in the text into Connected, Creative and Confident. From the results of the calculation of the closest distance and proximity of the neighboring obtained 10 popular hashtags. Creative Classifications become dominan type user.